Investigating the Impact of Systemic-theoretical Instruction on English Passive Structure Formation: Revisit of Vygotskian Concept-Formation Stance - Ghobadi, Tabasom (LANGUAGE ART, 2025)
Purpose: This study is organized to consider the teaching and learning of English passive structure for internalization by students using tool-oriented concepts. This study considered the impact of systemic-theoretical instruction (STI) on passive structure formation among Iranian EFL learners. Design/methodology/approach: In such doing, first, an OPT test was administered among 12 EFL learners studying in Tehran, Iran. Based on the OPT scores, 50 out of 68 participants were randomly chosen, which were divided into control and experimental groups. As the basic procedure, Concept Based Instruction (CBI) principles were taught twice a week, lasting eight weeks. After finishing treatment, a posttest focusing on English passive structure was given to the learners. Findings: The content of posttest was identical to the pretest. Independent sample t-test was applied to analyze the findings. Findings revealed that a substantial difference exists in the performance of the experimental and control groups in learning passive structure in posttest. The participants in the experimental group had better performance than control groups regarding English passive structure. Finally, the theoretical and pedagogical implications of the study were presented. Research limitations/implications: This research will be beneficial to educators, scholars, students, and parents. However, the key factors were limited to a small sample from selected institutions and cities, which cannot be used to generalize to a large population. Practical implications: Through applying the orientation tools in a top-down manner, English learners can reinforce theoretical recognition in practice, while accessing experiential knowledge and extending its use to new contexts. Through focusing on conceptual categories, learners can broaden their knowledge of important related concepts in passive structure. Social implications: Findings of study indicated that learning English passive structures increases in the following ways. First, pedagogically, in the orienting stage, learners can direct their learning by counting on the basic characteristics expressed by the conceptual categories. The same categories applied for teaching provide the same teaching-learning sequence, thereby elevating theoretical awareness, understanding, and control of English passive verbs. Originality/value: This research tries to teach English passive structure through conceptual metaphor theory.